A rapid and robust translational model for testicular aging research - N. Schmid; Y. Stepanov; M. Offner; L. Scholz; C. Herrmann; S. Petkov; R. Behr; J. B. Stöckl; T. Fröhlich; A. Mayerhofer (Histochemistry and Cell Biology, 2026)
In humans, testicular peritubular cells (TPCs) form a small compartment surrounding the seminiferous tubules and, as shown previously, undergo age-related changes. How they may contribute to the age-associated decline of testicular functions is not well known. Likewise, the mechanisms of testicular aging in humans are not well examined. This is in part due to the lack of appropriate cellular models. We aimed to establish an aging model of TPCs, which is based on immortalized nonhuman primate (NHP) peritubular cells (iMKTPCs) from Callithrix jacchus . As shown previously by a comprehensive proteomic approach, they strongly resemble human TPCs but lack the human cell-intrinsic heterogeneity. Cellular senescence was robustly induced within 10 days upon exposure to 25 µg/mL bleomycin for 24 h. This resulted in increased β-galactosidase activity, enlarged cells, and elevated transcript levels of senescence-associated secretory phenotype (SASP) molecules ( IL1b , TNFa , CCL2 ). The ability to contract upon a stimulus was reduced, as shown in live cell imaging studies. Reduced proliferation among others was indicated by a decreased abundance of proliferating cell nuclear antigen (PCNA), evident in a proteomic analysis, which also revealed massive changes (341 significantly increased and 372 decreased proteins). Bioinformatics analysis indicated a marked reduction in several cell-motility–associated proteins, whereas proteins linked to extracellular exosomes, the cytoskeleton, and lysosomal pathways were increased in abundance. To conclude, bleomycin treatment causes a rapid and robust induction of cellular senescence in a translational testicular cell model of peritubular cells. This model will enable future studies aiming to explore mechanisms and consequences of testicular aging.

Ghost fishing by self-baited lost, abandoned or discarded pots in snow crab (Chionoecetes opilio) fishery - Kristine Cerbule; Bent Herrmann; Roger B. Larsen; Mengjie Yu (Journal for Nature Conservation, 2024)

Can pots be an alternative fishing gear to gillnets? A Mediterranean case study - M. Virgili; A. Petetta; B. Herrmann; K. Cerbule; S. Guicciardi; G. La Manna; L. Malvarosa; D. Li Veli; G. Barone; A. Lucchetti (Reviews in Fish Biology and Fisheries, 2024)
Small-scale coastal fisheries in the Mediterranean often employ gillnets, a widely used gear worldwide. The disadvantages of gillnets in this fishery include high bycatch levels of unwanted species and consequent discards. Moreover, spatial conflict with other gears and dolphin depredation often results in considerable economic loss. Alternative fishing methods are being tested. This study investigated whether, in small-scale fisheries in the Adriatic Sea, pots can ensure sustainable harvest of mantis shrimp ( Squilla mantis ), a major target demersal species in terms of landings, and possibly replace traditional gillnets. We adopted a multidisciplinary approach to investigate the catch efficiency, biological impact, and socio-economic effects of the two fishing methods. We found different species compositions in gillnet and pot catches. Gillnets yielded a greater number of discarded species of no commercial value, whereas pots caught a greater amount of mantis shrimp. Finally, a profit analysis indicated that pot fishery has the potential to increase profits for the commercial fishing industry. This study suggests that pots provide a more sustainable fishing method, both in terms of revenue and environmental impact.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Are rigid sorting devices necessary to control size selectivity in demersal trawl fisheries? - Bent Herrmann; Zita Bak-Jensen; Manu Sistiaga; Jesse Brinkhof; Roger B. Larsen; Eduardo Grimaldo; Kristine Cerbule; Enis N. Kostak; Morteza Eighani (Regional Studies in Marine Science, 2024)

Effect of grid section design on trawl size selectivity - Manu Sistiaga; Bent Herrmann; Jesse Brinkhof; Roger B. Larsen (Regional Studies in Marine Science, 2023)

Ghost fishing efficiency by lost, abandoned or discarded pots in snow crab (Chionoecetes opilio) fishery - Kristine Cerbule; Bent Herrmann; Eduardo Grimaldo; Jesse Brinkhof; Manu Sistiaga; Roger B. Larsen; Zita Bak-Jensen (Marine Pollution Bulletin, 2023)

Use of biodegradable materials to reduce marine plastic pollution in small scale coastal longline fisheries - Kristine Cerbule; Bent Herrmann; Željka Trumbić; Mirela Petrić; Svjetlana Krstulović Šifner; Eduardo Grimaldo; Roger B. Larsen; Jure Brčić (Journal for Nature Conservation, 2023)

Simple pot modification improves catch efficiency and species composition in a tropical estuary mud crab (Scylla serrata) fishery - V.R. Madhu; Sreelakshmi B. Anand; Kristine Cerbule; Bent Herrmann (Estuarine, Coastal and Shelf Science, 2023)

Impact of ground gear design on catch efficiency in demersal trawl fishery - Y.E. Fakıoğlu; G. Gökçe; H. Özbilgin; K. Cerbule; B. Herrmann (Regional Studies in Marine Science, 2023)

Effect of gillnet twine thickness on capture pattern and efficiency in the Northeast-Arctic cod (Gadus morhua) fishery - Ilmar Brinkhof; Bent Herrmann; Roger B. Larsen; Jesse Brinkhof; Eduardo Grimaldo; Jørgen Vollstad (Marine Pollution Bulletin, 2023)

Is there a limit to the potential effects of shortening lastridge ropes on the size selectivity of diamond mesh codends? - Manu Sistiaga; Bent Herrmann; Jesse Brinkhof; Roger B. Larsen; Juan Santos; Daniel Stepputtis; Ilmar Brinkhof; Nadine Jacques; Kristine Cerbule; Andrea Petetta; Elsa Cuende; Liz Kvalvik (Fisheries Research, 2023)

Citizen science’s transformative impact on science, citizen empowerment and socio-political processes - Julia von Gönner; Thora M. Herrmann; Till Bruckermann; Michael Eichinger; Susanne Hecker; Friederike Klan; Julia Lorke; Anett Richter; Ulrike Sturm; Silke Voigt-Heucke; Wiebke Brink; Christin Liedtke; et al. (Socio-Ecological Practice Research, 2023)
Citizen science (CS) can foster transformative impact for science, citizen empowerment and socio-political processes. To unleash this impact, a clearer understanding of its current status and challenges for its development is needed. Using quantitative indicators developed in a collaborative stakeholder process, our study provides a comprehensive overview of the current status of CS in Germany, Austria and Switzerland. Our online survey with 340 responses focused on CS impact through (1) scientific practices, (2) participant learning and empowerment, and (3) socio-political processes. With regard to scientific impact, we found that data quality control is an established component of CS practice, while publication of CS data and results has not yet been achieved by all project coordinators (55%). Key benefits for citizen scientists were the experience of collective impact (“making a difference together with others”) as well as gaining new knowledge. For the citizen scientists’ learning outcomes, different forms of social learning, such as systematic feedback or personal mentoring, were essential. While the majority of respondents attributed an important value to CS for decision-making, only few were confident that CS data were indeed utilized as evidence by decision-makers. Based on these results, we recommend (1) that project coordinators and researchers strengthen scientific impact by fostering data management and publications, (2) that project coordinators and citizen scientists enhance participant impact by promoting social learning opportunities and (3) that project initiators and CS networks foster socio-political impact through early engagement with decision-makers and alignment with ongoing policy processes. In this way, CS can evolve its transformative impact.

Evaluating the Safety of Intra-Articular Mitotherapy in the Equine Model: A Potential Novel Treatment for Osteoarthritis - Jennifer M. Cassano; Krzysztof Marycz; Marta Horna; Marcos Perez Nogues; Jessica M. Morgan; Daniel B. Herrmann; Larry D. Galuppo; Natalia Vapniarsky (Journal of Equine Veterinary Science, 2023)

Joint effects of climate, tree size, and year on annual tree growth derived from tree‐ring records of ten globally distributed forests - Kristina J. Anderson‐Teixeira; Valentine Herrmann; Christine R. Rollinson; Bianca Gonzalez; Erika B. Gonzalez‐Akre; Neil Pederson; M. Ross Alexander; Craig D. Allen; Raquel Alfaro‐Sánchez; Tala Awada; Jennifer L. Baltzer; Patrick J. Baker; et al. (Global Change Biology, 2022)
Tree rings provide an invaluable long‐term record for understanding how climate and other drivers shape tree growth and forest productivity. However, conventional tree‐ring analysis methods were not designed to simultaneously test effects of climate, tree size, and other drivers on individual growth. This has limited the potential to test ecologically relevant hypotheses on tree growth sensitivity to environmental drivers and their interactions with tree size. Here, we develop and apply a new method to simultaneously model nonlinear effects of primary climate drivers, reconstructed tree diameter at breast height (DBH), and calendar year in generalized least squares models that account for the temporal autocorrelation inherent to each individual tree's growth. We analyze data from 3811 trees representing 40 species at 10 globally distributed sites, showing that precipitation, temperature, DBH, and calendar year have additively, and often interactively, influenced annual growth over the past 120 years. Growth responses were predominantly positive to precipitation (usually over ≥3‐month seasonal windows) and negative to temperature (usually maximum temperature, over ≤3‐month seasonal windows), with concave‐down responses in 63% of relationships. Climate sensitivity commonly varied with DBH (45% of cases tested), with larger trees usually more sensitive. Trends in ring width at small DBH were linked to the light environment under which trees established, but basal area or biomass increments consistently reached maxima at intermediate DBH. Accounting for climate and DBH, growth rate declined over time for 92% of species in secondary or disturbed stands, whereas growth trends were mixed in older forests. These trends were largely attributable to stand dynamics as cohorts and stands age, which remain challenging to disentangle from global change drivers. By providing a parsimonious approach for characterizing multiple interacting drivers of tree growth, our method reveals a more complete picture of the factors influencing growth than has previously been possible.

Long-Term Impacts of Invasive Insects and Pathogens on Composition, Biomass, and Diversity of Forests in Virginia’s Blue Ridge Mountains - Kristina J. Anderson-Teixeira; Valentine Herrmann; Wendy B. Cass; Alan B. Williams; Stephen J. Paull; Erika B. Gonzalez-Akre; Ryan Helcoski; Alan J. Tepley; Norman A. Bourg; Christopher T. Cosma; Abigail E. Ferson; Caroline Kittle; et al. (Ecosystems, 2021)

Length Polymorphisms in the Angiotensin I-Converting Enzyme Gene and the Serotonin-Transporter-Linked Polymorphic Region Constitute a Risk Haplotype for Depression in Patients with Coronary Artery Disease - Thomas Meyer; Isabel Rothe; Julia Staab; Hans-Christian Deter; Stella V. Fangauf; Stefanie Hamacher; Martin Hellmich; Jana Jünger; Karl-Heinz Ladwig; Matthias Michal; Katja Petrowski; Joram Ronel; et al. (Biochemical Genetics, 2020)
Genetic variations affecting the course of depressive symptoms in patients with coronary artery disease (CAD) have not yet been well studied. Therefore, we set out to investigate whether distinct haplotypes of the two insertion/deletion polymorphisms in the serotonin-transporter-linked polymorphic region ( 5-HTTLPR ) and the angiotensin I-converting enzyme ( ACE ) gene located on chromosome 17 can be identified as risk factors for trajectories of depression. Clinical and genotyping data were derived from 507 depressed CAD patients participating in the randomized, controlled, multicenter Stepwise Psychotherapy Intervention for Reducing Risk in Coronary Artery Disease (SPIRR-CAD) trial, of whom the majority had an acute cardiac event before study inclusion. Depression scores on the Hospital Anxiety and Depression Scale (HADS) were assessed at baseline and at five follow-up time points up to 2 years after study entrance. At baseline, depression scores did not significantly differ between patients carrying the risk haplotype ACE D/D, 5-HTTLPR I/I ( n = 46) and the non-risk haplotypes ( n = 461, 10.9 ± 2.7 versus 10.4 ± 2.5, p = 0.254). HADS-depression scores declined from study inclusion during the first year irrespective of the genotype. At each follow-up time point, HADS-depression scores were significantly higher in ACE D/D, 5-HTTLPR I/I carriers than in their counterparts. Two years after study inclusion, the mean HADS depression score remained 1.8 points higher in patients with the risk haplotype as compared to subjects not carrying this haplotype (9.9 ± 4.2 versus 8.1 ± 4.0, p = 0.009). In summary, the presence of the ACE D/D, 5-HTTLPR I/I haplotype may be a vulnerability factor for comorbid depressive symptoms in CAD patients.

Differential Bioaccumulation of Mercury and Selenium in Stomach Contents and Tissues of Three Colorado, USA, Cutthroat Trout Populations - Scott J. Herrmann; Del Wayne R. Nimmo; James S. Carsella; Igor V. Melnykov; Christopher M. Kennedy; Kevin B. Rogers; Lynn M. Herrmann-Hoesing (Bulletin of Environmental Contamination and Toxicology, 2020)

Estimating Oceanic Crustal Structure from OBS Data Using Teleseismic P Wave Wavefield Continuation - Degao Zheng; Robert B. Herrmann; Xiaohui He (Pure and Applied Geophysics, 2019)

Reduced spontaneous low frequency oscillations as measured with functional near-infrared spectroscopy in mild cognitive impairment - Julia B. M. Zeller; Andrea Katzorke; Laura D. Müller; Judith Breunig; Florian B. Haeussinger; Jürgen Deckert; Bodo Warrings; Martin Lauer; Thomas Polak; Martin J. Herrmann (Brain Imaging and Behavior, 2019)

Effect of fish length and nutritional condition on the fecundity of distressed Atlantic cod Gadus morhua from the Baltic Sea - M. Mion; A. Thorsen; F. Vitale; J. Dierking; J. P. Herrmann; B. Huwer; B. von Dewitz; M. Casini (Journal of Fish Biology, 2018)
The disappearance of larger individuals and the decrease in individual body condition suffered by Atlantic cod Gadus morhua in the eastern Baltic during the past two decades can be expected to affect the stock reproductive output. To investigate this, female G. morhua were collected during the spawning and pre‐spawning period in 2015−2016. The current individual potential fecundity ( F P ) of eastern Baltic G. morhua was estimated and analysed in relation to total length ( L T ) and indices of nutritional status such as body condition ( K ) and hepato‐somatic index ( I H ) using generalized linear models. In addition, the current prevalence of atresia and its potential relation to K were investigated. Moreover, a calibration curve to estimate F P from oocyte diameter, based on the autodiametric oocyte counting method, was established for the first time for eastern Baltic G. morhua and can be used for future fecundity studies on this stock. The results showed that F P was mainly positively related to fish length, but K and I H also contributed significantly to the variation in F P . The model predicted that fish with K = 1·2 have a F P 51% higher than fish of the same L T with K = 0·8. The prevalence of fecundity regulation by atresia was 5·8%, but it was found only in fish in the pre‐spawning maturity stage and with low K . Temporal changes in biological features such as the length composition and individual body condition of eastern Baltic G. morhua , should be accounted for when estimating stock reproductive potential.

Measurements of PM10 ions and trace gases with the online system MARGA at the research station Melpitz in Germany – A five-year study - B. Stieger; G. Spindler; B. Fahlbusch; K. Müller; A. Grüner; L. Poulain; L. Thöni; E. Seitler; M. Wallasch; H. Herrmann (Journal of Atmospheric Chemistry, 2018)

Prolonged suppressive antibiotic therapy for prosthetic joint infection in the elderly: a national multicentre cohort study - V. Prendki; T. Ferry; P. Sergent; E. Oziol; E. Forestier; T. Fraisse; S. Tounes; S. Ansart; J. Gaillat; S. Bayle; O. Ruyer; F. Borlot; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Field studies measuring the aerosolization of endotoxin during the land application of Class B biosolids - R. F. Herrmann; R. J. Grosser; D. Farrar; R. B. Brobst (Aerobiologia, 2017)

Large-scale genetic census of an elusive carnivore, the European wildcat (Felis s. silvestris) - Katharina Steyer; Robert H. S. Kraus; Thomas Mölich; Ole Anders; Berardino Cocchiararo; Christiane Frosch; Alexander Geib; Malte Götz; Mathias Herrmann; Karsten Hupe; Annette Kohnen; Matthias Krüger; et al. (Conservation Genetics, 2016)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Semiautomated quantitative image analysis of glomerular immunohistochemistry markers desmin, vimentin, podocin, synaptopodin and WT-1 in acute and chronic rat kidney disease models - J. Funk; V. Ott; A. Herrmann; W. Rapp; S. Raab; W. Riboulet; A. Vandjour; E. Hainaut; A. Benardeau; T. Singer; B. Jacobsen (Histochemistry and Cell Biology, 2016)

Differential Accumulation of Mercury and Selenium in Brown Trout Tissues of a High-Gradient Urbanized Stream in Colorado, USA - S. J. Herrmann; D. R. Nimmo; J. S. Carsella; L. M. Herrmann-Hoesing; J. A. Turner; J. M. Gregorich; B. D. Vanden Heuvel; R. B. Nehring; H. P. Foutz (Archives of Environmental Contamination and Toxicology, 2016)

Photocatalytic abatement results from a model street canyon - M. Gallus; R. Ciuraru; F. Mothes; V. Akylas; F. Barmpas; A. Beeldens; F. Bernard; E. Boonen; A. Boréave; M. Cazaunau; N. Charbonnel; H. Chen; et al. (Environmental Science and Pollution Research, 2015)

Mutations of the SLIT2–ROBO2 pathway genes SLIT2 and SRGAP1 confer risk for congenital anomalies of the kidney and urinary tract - Daw-Yang Hwang; Stefan Kohl; Xueping Fan; Asaf Vivante; Stefanie Chan; Gabriel C. Dworschak; Julian Schulz; Albertien M. van Eerde; Alina C. Hilger; Heon Yung Gee; Tracie Pennimpede; Bernhard G. Herrmann; et al. (Human Genetics, 2015)

Chemical properties of HULIS from three different environments - T. B. Kristensen; L. Du; Q. T. Nguyen; J. K. Nøjgaard; C. Bender Koch; O. Faurskov Nielsen; A. G. Hallar; D. H. Lowenthal; B. Nekat; D. van Pinxteren; H. Herrmann; M. Glasius; et al. (Journal of Atmospheric Chemistry, 2015)

H-D exchange on graphite–potassium intercalation compounds - Siegbert Rummel; Michael Herrmann; Manfred Wahren; Safar M. Yunusov; Margarita A. Ilatovskaya; Yuri B. Isaev; N. D. Lapkina; Yuri N. Novikov; Vladimir B. Shur (Isotopes in Environmental and Health Studies, 2012)

Seasonal characteristics of tropical marine boundary layer air measured at the Cape Verde Atmospheric Observatory - L. J. Carpenter; Z. L. Fleming; K. A. Read; J. D. Lee; S. J. Moller; J. R. Hopkins; R. M. Purvis; A. C. Lewis; K. Müller; B. Heinold; H. Herrmann; K. Wadinga Fomba; et al. (Journal of Atmospheric Chemistry, 2010)

Complete nucleotide sequence of the Oenothera elata plastid chromosome, representing plastome I of the five distinguishable Euoenothera plastomes - H. Hupfer; M. Swiatek; S. Hornung; R. G. Herrmann; R. M. Maier; W.-L. Chiu; B. Sears (Molecular Genetics and Genomics, 2008)

Secondary structure and distribution of fusogenic LV-peptides in lipid membranes - J. Ollesch; B. C. Poschner; J. Nikolaus; M. W. Hofmann; A. Herrmann; K. Gerwert; D. Langosch (European Biophysics Journal, 2008)

Intragenic deletion in the LARGE gene causes Walker-Warburg syndrome - Jeroen van Reeuwijk; Prabhjit K. Grewal; Mustafa A. M. Salih; Daniel Beltrán-Valero de Bernabé; Jenny M. McLaughlan; Caroline B. Michielse; Ralf Herrmann; Jane E. Hewitt; Alice Steinbrecher; Mohamed Z. Seidahmed; Mohamed M. Shaheed; Abdullah Abomelha; et al. (Human Genetics, 2007)

Abschätzung des akuten Risikos durch Pflanzenschutzmittel-Rückstände in Lebensmitteln auf der Basis von Daten aus amtlicher Überwachung und Eigenkontrollen - U. Banasiak; M. Herrmann; K. Hohgardt; B. Michalski; C. Sieke (Journal of Consumer Protection and Food Safety, 2007)

Ground-Motion Scaling in the Western Alps - Paola Morasca; Luca Malagnini; Aybige Akinci; Daniele Spallarossa; R. B. Herrmann (Journal of Seismology, 2006)

Comparative analysis of adenoviral transgene delivery via tail or portal vein into rat liver - J. Herrmann; B. Abriss; E. van de Leur; S. Weiskirchen; A. M. Gressner; R. Weiskirchen (Archives of Virology, 2004)

A long-term study on the population dynamics of the grape leafhopper ( Empoasca vitis ) and antagonistic mymarid species - S. Bll; J. V. Herrmann (Journal of Pest Science, 2004)

Genetic distinction of wildcat ( Felis silvestris ) populations in Europe, and hybridization with domestic cats in Hungary - M. Pierpaoli; Z. S. Birò; M. Herrmann; K. Hupe; M. Fernandes; B. Ragni; L. Szemethy; E. Randi (Molecular Ecology, 2003)
The genetic integrity and evolutionary persistence of declining wildcat populations are threatened by crossbreeding with widespread free‐living domestic cats. Here we use allelic variation at 12 microsatellite loci to describe genetic variation in 336 cats sampled from nine European countries. Cats were identified as European wildcats ( Felis silvestris silvestris ), Sardinian wildcats ( F. s. libyca ) and domestic cats ( F. s. catus ), according to phenotypic traits, geographical locations and independently of any genetic information. Genetic variability was significantly partitioned among taxonomic groups ( F ST = 0.11; R ST = 0.41; P F ST = 0.07; R ST = 0.06; P

Swiss Mattenklee landraces, a distinct and diverse genetic resource of red clover (Trifolium pratense L.) - R. Kölliker; D. Herrmann; B. Boller; F. Widmer (Theoretical and Applied Genetics, 2003)

Effects of selective inactivation of individual genes for low-molecular-mass subunits on the assembly of photosystem II, as revealed by chloroplast transformation: the psbEFLJ operon in Nicotiana tabacum - M. Swiatek; R. E. Regel; J. Meurer; G. Wanner; H. B. Pakrasi; I. Ohad; R. G. Herrmann (Molecular Genetics and Genomics, 2003)

Scenarios for Modeling Multiphase Tropospheric Chemistry - D. Poppe; B. Aumont; B. Ervens; H. Geiger; H. Herrmann; E.-P. Röth; W. Seidl; W. R. Stockwell; B. Vogel; S. Wagner; D. Weise (Journal of Atmospheric Chemistry, 2001)

N budget and NH3 exchange of a grass/clover crop at two levels of N application - B. Herrmann; S. K. Jones; J. Fuhrer; U. Feller; A. Neftel (Plant and Soil, 2001)

Biosphere-atmosphere interactions of ammonia with grasslands: Experimental strategy and results from a new European initiative - M.A. Sutton; C. Milford; E. Nemitz; M.R. Theobald; P.W. Hill; D. Fowler; J.K. Schjoerring; M.E. Mattsson; K.H. Nielsen; S. Husted; J.W. Erisman; R. Otjes; et al. (Plant and Soil, 2001)

CAPRAM2.3: A Chemical Aqueous Phase Radical Mechanism for Tropospheric Chemistry - H. Herrmann; B. Ervens; H.-W. Jacobi; R. Wolke; P. Nowacki; R. Zellner (Journal of Atmospheric Chemistry, 2000)

Proving the Authenticity of Ancient DNA by Comparative Genomic Hybridization - S. Hummel; B. Herrmann; J. Rameckers; D. Müller; K. Sperling; H. Neitzel; H. Tönnies (The Science of Nature, 1999)

Diurnal changes in xylem pressure and mesophyll cell turgor pressure of the lianaTetrastigma voinierianum: The role of cell turgor in long-distance water transport - F. Thrmer; J. J. Zhu; N. Gierlinger; H. Schneider; R. Benkert; P. Gener; B. Herrmann; F. -W. Bentrup; U. Zimmerniann (Protoplasma, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Effect of dimethicone (polysilane gel) on the stereoselective pharmacokinetics of ketoprofen - N. Presle; F. Lapicque; P. Gillet; M.-A. Herrmann; B. Bannwarth; P. Netter (European Journal of Clinical Pharmacology, 1998)

Book Reviews - B. Herrmann (The Science of Nature, 1998)

Book Reviews - B. Herrmann; B. Schweitzer; N. Biedinger (The Science of Nature, 1998)

Approaches to the prevention and control of skin cancer - Scott R. Cummings; Mary K. Tripp; Nancy B. Herrmann (Cancer and Metastasis Reviews, 1997)

Intraepidemic variants of influenza virus H3 hemagglutinin differing in the number of carbohydrate side chains - W. Seidel; F. Knkel; B. Geisler; W. Garten; B. Herrmann; L. Dhner; H. -D. Klenk (Archives of Virology, 1991)

Differences of nucleoproteins of human and avian influenza a virus strains shown by polyacrylamide gel electrophoresis and by the peptide mapping technique - B. Geisler; W. Seidel; B. Herrmann; L. Dhner (Archives of Virology, 1986)